Observation on Hydatid Cyst Infection in Kordestan Province (West of Iran) using Epidemiological and Seroepidemiological Criteria - L Akhlaghi; J Massoud; A Housaini (Tehran University of Medical Sciences, 2005)
Echinococcosis is the major helminthic parasitic infection in Iran. The health hazard and economic loss in man and livestock is significant. In this study 3 major topics as the prevalence of hydatid cyst in human population, in livestock and echinococcosis in stray dogs, were studied. Total of 1114 serum samples in different age groups in Sanandaj and Divandareh area of Kurdestan province in west of Iran were examined by indirect immunoflurecent test (IFA). In Sanandaj area 3.3% and in Divandareh 9.5% of serum samples were positive for hydatidosis. In livestock using abattoir inspection the rate of infection was 51.9% and 28.02% for sheep and cattle, respectively. Nine stray dogs (44%) autopsied in Sanandaj were positive for Echinococcosis.